SURVEY TENTANG PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 19 SURABAYA - PUTRI EKA DESVIA MIASTUTIE (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study aims to determine the type of evaluation tool in SMA 19 Surabaya and the reasons teachers use this type of tool evaluation and an evaluation tool to determine the feasibility of the use of evaluation tools. This study is a descriptive research with quantitative approach. The results showed that the evaluation tool used was a kind of test is multiple choice and a description of, among others, daily tests, midterm replay, and replay the end of the semester. Based on the review of the results obtained expert evaluation tool that accounting evaluation tool deserves to be tested, and the results of quantitative analysis of evaluation tools considered valid, reliable, well differentiated power, about the difficulty level of medium. Keywords: Evaluation Tool